Research in environmental fluid mechanics on sediment transport of steep beach - Ku Nurizwanshah Ku Azame (2017)
Environmental Fluid Mechanics in recent years have had an increased concern from the world, from the likes of engineers and environmentalists, due to the accelerated pace of modern engineering and how it effects the environment. Many projects and movements have been kick started to maintain and preserve the environment for our future generations. Hence, engineers of the world are looking more in depth on the move towards a more environmentally friendly future. Thus, this report will provide a profound insight on the research of fluid mechanics of environmental interfaces focusing on sediment transport on steep beach effects due to unnaturally form from engineering of land reclamation. It will begin with an introduction of the research background, scope, objective and as well as the outline of this research report. Sedimentation transport theories in fluid mechanics such as hydraulic properties of sediments, bed load calculation and more will be discussed in depth. These theories will stem upon the fundamentals of different type of transport of dispersion of unnatural sand and sediments introduced to coastal ecosystem with the likes of land reclamation. Following on will be emphasizing on the environmental engineering aspect of mode of sedimentation. Finally, the report will cover on experimentation methodology, analysis and results of sudden sedimentation pollution and impact of sediment movement in aquatic environment mainly in coastal and shorelines ecosystem Aspects emphasize on the positive aspects and also the environmental drawbacks which may arise from future reclamation plans are also covered within this research paper.